UJI KINERJA KATALIS Cu-ZnO/AI2O3 YANG DIPREPARASI DENGAN METODE KOPRESIPITASI UNTUK KONVERSI GLISEROL MENJADI PROPANADIOL - R. Sarwono; K. C. Sembiring; D. S. Kusuma; S. Tursiloadi (Research Center for Chemistry - LIPI, 2013)
Glycerolis the side product of esterificationprocess of edible oil into ester which is called as biodiesel. Conversion of glycerol into propanediol (PDO) involved many steps of reactions. Dehydration of Glycerol to 3- hydroxypropanalisstarted by breaking c-o bond, continued by hydrogenation reaction of 3-hydroxypropanal to produce 1,3-PDO. If the dehydration result of glycerol is acetol, the hydrogenation of acetol will produce 1,2-PDo. The dehydration reaction is depend on the strength of catalyst acidity or metalion Cu;itwill enhance the reactionselectivity toproduce 1,2 or 1,3-PDO. The strength ofCu-ZnO/A1203 catalyst prepared by coprecipitation method is 2.8 mmollgram. The glycerol conversion is almost 100% with 1,2-PDO as the main product and no 1,3-PDO wasobtained.Keywords: glicerol, co-precipitaion, catalyst, dehydration,PDO